Systematic Literature Review (SLR) : Problematika Dalam Penulisan Karya Ilmiah - Nabila, Nabila; Usiono Usiono (Journal of Creative Student Research, 2024)
For educational institutions to continue to progress and develop, there are several indicators that must be met. One of them is scientific work that is recognized by academics. However, in its implementation, there are various obstacles faced by researchers. Given these problems, this study aims to identify the main challenges in writing scientific papers. This research uses the Systematic Literature Review (SRL) method whose data comes from articles found on the Google Schoolar website published in 2020-2024. With the SLR method, systematic interpretation and identification are carried out. The results of this study indicate that the main challenge in writing scientific papers is the lack of understanding of automatic citation and bibliography applications, namely the mendeley application. Based on the results, the research conclusion suggests that an effective solution to the challenges of writing scientific papers is in-depth training on the use of the mendeley application to support quality scientific paper.